Drive System Based on Five-phase Stepping Motor under Microstepping/nanostepping Mode. (2015) - Morar, Alexandru
Abstract: Hybrid stepper motor is one of the primary candidates for direct drive motor due its high torque and low speed, but the vibration it produces is a major drawback to use it in applications. The micro-step (nano-step) method is typically used to reduce the vibration and to obtain high resolution motor steps, which divides a single step into many micro-steps (nano-steps). PWM (Pulse Width Modulation) is the most common method to control the current, flowing through the windings. This paper presents the development and implementation of nanostepping controlling five-phase stepping motor. Nanostepping system achieves up to 1/1000 of full step of five-phase stepper motor. The proposed system achieves nanostepping using PWM signals generated by digital signal controller dsPIC 30F4011. Low vibration, low noise and improved controllability are achieved using microstepping (nanostepping). The application we developed is aimed for use in a low cost system.